GAJARDOITE-(NH4), (NH4)As3+ 4O6Cl2[(Ca0.5□0.5)(H2O)5], A NEW MINERAL FROM THE KHOVU-AKSY DEPOSIT, EASTERN SIBERIA, RUSSIA - A.V. Kasatkin; V.V. Gurzhiy; N.V. Chukanov; A.A. Agakhanov; R. Škoda; D.I. Belakovskiy (Минералогия)
The new mineral gajardoite-(NH4), ideally (NH4)As3+4O6Cl2[(Ca0.5□0.5)(H2O)5], is found at the Khovu-Aksy Ni-Co deposit, Republic of Tyva, Russia. Gajardoite-(NH4) occurs as tiny lamellar coarsely hexagonal or irregular curved and divergent crystals up to 0.01 mm in size. The crystals are combined in groups, rosette-like clusters or spherulitic aggregates up to 0.2 mm, which are intimately intergrown with annabergite, arsenolite, and pharmacolite on a matrix of skutterudite, safflorite, and other minerals. The new mineral is colorless, white in aggregates, transparent with a white streak and a vitreous lustre. It is brittle, with a perfect cleavage on {001}. The Mohs hardness is ~1½. The calculated density (Dcalc) is 2.583 g/cm3 .Gajardoite-(NH4) is optically non-pleochroic, uniaxial (–), ω = 1.745(10), ε = 1.558(5) (589 nm). The chemical composition determined by electron microprobe (wt. %, H2O content calculated by stoichiometry) is as follows: (NH4)2O 3.17, Na2O 0.40, K2O 1.07, CaO 5.28, As2O3 67.25, Cl 12.21, H2O 15.30, O=Cl –2.76, total 101.92. The empirical formula based on four As and 11 O atoms per formula unit is [(NH4)0.72K0.13Na0.08]Σ0.93Ca0.55As3+4O6Cl2.03(H2O)5. Gajardoite-(NH4) is hexagonal, space group P6/mmm; the unit-cell parameters are as follows: a = 5.263(3), c = 16.078(5) Å, V = 385.8(5) Å3 , Z = 1. The strongest lines of the powder X-ray diffraction pattern [d, Å (I, %) (hkl)] include 16.08 (34) (001), 5.36 (34) (003), 4.565 (41) (100), 3.466 (23) (103), 2.637 (100) (110), 2.360 (25) (113). Gajardoite-(NH4) is an ammonium analog of gajardoite KCa0.5As3+4O6Cl2 • 5H2O. Their structural identity is confirmed by powder X-ray diffraction and infrared and Raman spectroscopy.